The Role of Nitrogen‐doping in the Catalytic Transfer Hydrogenation of Phenol to Cyclohexanone with Formic Acid over Pd supported on Carbon Nanotubes. Issue 42 (18th June 2021) - Hu, Bin; Li, Xiaoyu; Busser, Wilma; Schmidt, Stefan; Xia, Wei; Li, Guangci; Li, Xuebing; Peng, Baoxiang
Abstract: Highly selective one‐step hydrogenation of phenol to cyclohexanone, an important intermediate in the production of nylon 6 and nylon 66, is desirable but remains a challenge. Pd nanoparticles supported on nitrogen‐ and oxygen‐functionalized carbon nanotubes (NCNTs, OCNTs) were prepared, characterized, and applied in the hydrogenation of phenol to cyclohexanone to study the effect of N‐doping. Almost full conversion of phenol with high selectivity to cyclohexanone was achieved over Pd/NCNT under mild reaction conditions using either H2 or formic acid (FA) as a hydrogen source. The effects of reaction temperature and FA/phenol ratio and the reusability were investigated. Separate FA decomposition experiments without and with the addition of phenol were performed to investigate the reaction mechanism, especially the deactivation behavior. Deactivation was observed for both catalysts during the FA decomposition, while only Pd/OCNT rather than Pd/NCNT was deactivated in the transfer hydrogenation with FA and the FA decomposition in the presence of phenol, indicating the unique role of N‐doping. Therefore, we assume that deactivation is caused by the strongly bound formates on the active Pd sites, suppressing further FA decomposition and/or transfer hydrogenation on Pd. The nonplanar adsorption of phenol on NCNTs via weak O−H⋅⋅⋅N interactions enables the occurrence of the subsequent hydrogenation by adsorbed formate on Pd. Abstract : Pd/OCNT is deactivated during the transfer hydrogenation of phenol with formic acid to cyclohexanone because of the full coverage of formate on Pd. By comparison, Pd/NCNT is highly active and selective in the transfer hydrogenation and deactivation does not occur. The nonplanar adsorption of phenol on NCNTs via weak O−H⋅⋅⋅N interactions enables the transfer hydrogenation with the adsorbed formate on Pd.